The Predictive Role of Morphological Indicators in Enhancing Volleyball Players’ Sports Performance - M., Khayrullaeva L.; A., Kurbanova M. (American Journal of Biodiversity, 2026)
The leading factors in the formation of physique or somatic status in various types of sports are the total dimensions of the body, its mass composition components. The somatic substantiation of sports skills in individual types and directions of sports is not constant. Views on this issue change as the technique of performing individual exercises improves, the rules of competitions are modernized with the use of new models of sports equipment. However, it is possible to determine the specialty to which an athlete belongs by his physique, since the main factors of somatic status are characteristic for each sports specialty.